Ceftolozane-tazobactam in combination with fosfomycin for treatment of MDR/XDR P. aeruginosa infective endocarditis. (October 2019) - Prescott, A.; Kennedy, S.; Howard, P.; Collyns, T.; Gilleece, M.H.; Pirone, F.; Baig, M.W.; Donnellan, C.; Sandoe, J.A.T.
Abstract: Background: Infective endocarditis (IE) due to multi-drug (MDR) and extensively drug-resistant (XDR) Pseudomonas aeruginosa is rare. MDR P. aeruginosa infections are increasingly reported worldwide, and the choice of effective antimicrobials is limited. Ceftolozane-tazobactam is a new antimicrobial combination with activity against many resistant strains of P. aeruginosa, but there are limited data on its use in complex infections. Methods: We present the first reported cases of XDR P. aeruginosa IE and MDR P. aeruginosa intravascular catheter-related bloodstream infection [CRBSI] with possible IE to be treated with ceftolozane-tazobactam in combination with other agents. Results: Patient 1 completed seven weeks treatment with ceftolozane-tazobactam and fosfomycin, in combination with valve replacement, for XDR P. aeruginosa IE and is 2 year post-treatment without signs of relapse. Patient 2 completed 4 weeks treatment with ceftolozane-tazobactam and fosfomycin for MDR P. aeruginosa intravascular CRBSI with possible IE and went 8 months before MDR P. aeruginosa was cultured again from a line culture and tip. Conclusions: These cases highlight the difficulties of managing IE caused by MDR and XDR P. aeruginosa infections and indicate that ceftolozane-tazobactam may be effective when there are no alternative beta-lactams. Highlights: Diagnosis of P. aeruginosa infective endocarditis can be challenging. Management of IE caused by MDR and XDR P. aeruginosa infections is complex. Ceftolozane-tazobactam may be effective when there are no alternative beta-lactams.